Analisis Pembiayaan Bermasalah Pada Akad Murabahah Bil Wakalah di BMT Al Ishlah Kecamatan Telanaipura Kota Jambi - Yunisa Putri Elsanti; Ahmad Tarmidzi; Erwin Saputra Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Murabaha bil wakalah financing at BMT AL-Ishlah, Jambi, experienced payment problems. The Islamic finance industry is growing rapidly, but problematic financing is a challenge. The research aims to identify the causes and strategies for solving murabahah bil wakalah financing problems. This research uses a qualitative approach, data collection is carried out by observation, interviews and documentation. Data analysis includes data reduction, data presentation, and conclusion verification. The research focuses on identifying internal and external factors that cause financing problems and exploring solutions to resolve them. The results of this research are internal factors including inaccurate credit analysis and inadequate application of the 5C principles. External factors include economic conditions, the COVID-19 pandemic, and customer behavior. Solving problems through non-litigation approaches such as friendship, financing restructuring and financial assistance. Research finds that proper handling can reduce the risk of problematic financing and support the sustainability of BMT in the Islamic finance industry.